Pancasila vs Polarisasi: Pertarungan Nilai dalam Membentuk Sikap Toleransi Siswa Masa Kini - Chrisandes Kurniawan Naikofi; Petrus Alexander Tamonob; Arianti Angelita Naitboho; Aply Rosyanti Halla; Ferawati Bana; Fadil Mas’ud; Rahyudi Dwiputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the tension between the foundational values of Pancasila and the growing trend of sociopolitical polarization among today’s students. It seeks to explore how the core principles of Pancasila such as unity, tolerance, and social justice shape students’ attitudes in real-life interactions, especially within environments increasingly influenced by digital communication. The research examines how digital media algorithms, ideological segmentation, and identity-based online communities contribute to the formation of polarized perspectives among students. These digital dynamics often intensify emotional responses, reinforce echo chambers, and create fragmented spaces of interaction that challenge the implementation of Pancasila in everyday life. Using a qualitative descriptive design, this study employs interviews, observations, and document analysis conducted in several Indonesian schools. The findings reveal that although students possess a strong conceptual understanding of Pancasila, their practical application of tolerance and mutual respect is frequently disrupted by polarized narratives circulating both online and offline. Social media interactions, in particular, expose students to misinformation, provocative content, and identity-based conflicts that shape how they perceive others. The study highlights the importance of revitalizing Pancasila education by integrating digital literacy skills and dialogic learning. Digital literacy enables students to critically evaluate online information, recognize bias, and navigate algorithm-driven content, while dialogic learning encourages reflective conversations that promote empathy and ethical awareness. Ultimately, the research concludes that Pancasila education must adapt to the realities of the digital era in order to foster resilient, tolerant, and socially responsible young citizens.